Effect of acid-methanol treatment on the physicochemical and structural characteristics of cassava and maize starches - Ferrini, Luara M. K. [UNESP]; Rocha, Thais S. [UNESP]; Demiate, Ivo M.; Franco, Celia M. L. [UNESP] (Wiley-Blackwell, 2008)
Physicochemical, structural and morphological characteristics of maize and cassava starches treated with 0.36% concentrated HCl in anhydrous methanol at WC for 1-8 h were analyzed and compared. Average yield of modified starch was about 97% for both starches. The solubility of the acid-methanol treated starches increased with temperature and after 3 h of treatment reached 93% for maize starch and 97% for cassava starch at 95 degrees C. After 8 h of treatment, the average size of the cassava starch granules decreased from 14.9 to 11.1 mu m. The action of acid-methanol on the maize starch was more subtle, reducing the granule average size from 11.8 to 11.3 mu m. Scanning electron micrographs showed that the granule surfaces were rough and exfoliated after treatment suggesting exocorrosion that was more evident for cassava starch. From GPC, it was noted that amylose and amylopectin were partially degraded during treatment. Starch crystallinity gradually increased with duration of treatment. The amylose content decreased from 21.4 to 18.8% and from 26.3 to 23.0% and the intrinsic viscosity was reduced from 2.36 to 0.21 and from 1.85 to 0.04 for cassava and maize starches, respectively. The gelatinization temperatures increased whereas pasting viscosities decreased with reaction time, especially for cassava starch. These results suggested that the attack of acid-methanol, which was more effective on cassava starch granules, occurred preferentially in the amorphous areas located in the granule periphery and composed of amylose and amylopectin.
Keywords: Starch; acid-methanol treatment; Structural characteristics; Physicochemical properties